2022
DOI: 10.18662/po/13.2/461
|View full text |Cite
|
Sign up to set email alerts
|

Enterpreneship Transformation in the Context of the Digitization of Business Processes

Abstract: This article examines the transformation of enterprises activity in terms of digitalization of business processes. The rapid and global spread of information and communication technologies contributes to the development of the digital economy and causes changes in the economic environment, which leads to the transformation of business activities, methods of transactions and the level of connections between economic entities. Globalization and digitalization of the economy transform the key characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…Scholars note that the legal framework of Ukraine regarding the regulation of the e-commerce sector is narrower than, for example, in the U.S. and the EU, but it has advantages: greater freedom of entrepreneurs in the Internet space. Lytvyn et al (2022) are also proponents of a broad approach and note that e-commerce includes not only e-commerce but also information exchange, e-capital movement, e-commerce, e-money, e-marketing, e-banking, and e-insurance services.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Scholars note that the legal framework of Ukraine regarding the regulation of the e-commerce sector is narrower than, for example, in the U.S. and the EU, but it has advantages: greater freedom of entrepreneurs in the Internet space. Lytvyn et al (2022) are also proponents of a broad approach and note that e-commerce includes not only e-commerce but also information exchange, e-capital movement, e-commerce, e-money, e-marketing, e-banking, and e-insurance services.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In their opinion, the competitiveness of the socio-economic systems is the to produce and sell competitive products that will have competitive advantages compared to similar products of competitors in a certain period of time in a certain market, as well as to form the dynamics of the effectiveness of positive changes in the main indicators of profitability and increase in cost companies capital. Some groups of scientists [4][5][6] consider the increase in competitiveness as a long-term process carried out in accordance with the chosen strategy for the development of an socio-economic systems; a number of measures can be identified that provide socio-economic systems with the achievement of competitive advantages, namely: reducing the cost of production; increasing its priority; change in the quality and technical parameters of products; identifying flaws in competitor products; introduction of innovations; identifying the advantages of own products in comparison with substitutes; use of price factors to increase competition; influence on the consumer through advertising, providing a loan; search for new areas of product use.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Нарешті, важливимє економічний контекст та інтереси різних секторів суспільства, котрі долучені до системи природокористування. Особливістю в даному випадку є те, що Україна має складну економіку, де природні ресурси часто використовуються як джерело доходів і саме це суттєво впливає проблематику раціональності господарської діяльності[8]. Відповідно, інструменти інституційного забезпечення повинні бути спрямовані на збалансоване задоволення потреб економіки, соціальних груп та екологічних цінностей.Зважаючи на специфіку сьогодення, важливо також враховувати міжнародний контекст та зв'язки з міжнародними організаціями та угодами, що стосуються природокористування.…”
unclassified